EVALUASI KELEBIHAN DAN KETERBATASAN PLATFORM LOW- CODE DALAM PENGEMBANGAN SISTEM INFORMASI PERUSAHAAN - Herwis Gultom; Jaka Oktavian; Ahmad Afgani; Deby Ardiansyah; Khoirul Umam; Maya Komariah; Rio Adriana; Rivai Syukur Ramadhan; Eldrick Rifaldo (Abdi Jurnal Publikasi, 2025)
The rapid advancement of digital technology compels companies to continuously adapt by developing information systems that are both efficient and responsive to dynamic business needs. Low-code platforms have emerged as an alternative solution that accelerates system development without requiring extensive programming skills. This study aims to evaluate the advantages and limitations of low-code platforms in the context of enterprise information system development. The research employs a combination of literature review, observations of implementations in several companies, and interviews with IT practitioners. The evaluation results indicate that low-code platforms offer several strengths, including faster development times, easier integration, and enhanced collaboration between technical and non- technical teams. However, certain limitations were also identified, such as constraints in handling complex customizations, risks of vendor lock-in, and challenges related to scalability and data security management. Therefore, the adoption of low-code platforms should be strategically considered based on the specific needs and complexity of the systems being developed.